Antioxidant effects and anti-aging characteristics of Leonurus japonicus H. ethanol extracts - JeGal, Mi; Jo, Youn Kyoung; Moon, Hwan Sig; Kwon, Ki Han (Progress in Nutrition, 2018)
Leonurus japonicus H. is a biennial wild plant that grows naturally in Asian countries such as Korea, China and Japan and belongs to Labiatae and has been used in lowering blood pressure, promoting urination, as a pain-killer, sedation and in promoting menstruation. In this study, Leonuri herba’s antioxidant function, improvement were investigated. L. japonicus H. extract was fractioned into Hexane, Ethyl Acetate, Water, H2O, 30% EtOH, 60% EtOH and 100% EtOH. The investigator carried out an experiment of confirming the capability of superoxide erasure by using the DPPH technique of antioxidant experiment and Xanthine oxidase hypoxanthine and measured the activation of antioxidant with ABTS technique. This Study showed that the 30% EtOH fraction was highest in antioxidant effect. Collagense synthesis was significantly increased in the experiment of anti-wrinkle effcet. All the L. japonicus H. extracts inhibited the generation of H2O2 in a dose dependent manner. Based on the above study findings, the anti-aging effect of 30% EtOH fraction of L. japonicus H. was most excellent. In conclusion, the rutin and adenosine of L. japonicus H. extract had a strong antioxidant function. If it is used in cosmetics, a variety of natural functional cosmetics, such as excellent natural moisturizers, antioxidant agents and anti-aging agent, can be developed.